2006
DOI: 10.1148/radiol.2381041234
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Displaceable and Nondisplaceable Meniscal Tears at Kinematic MR Imaging of the Knee

Abstract: Displaceable meniscal tears usually have longitudinal, radial, or complex configurations; such tears are associated with substantial ipsilateral collateral ligament lesions and pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
42
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 26 publications
1
42
0
Order By: Relevance
“…In this study both sensitivity and specificity values of kinematic MRI had been found to be higher than conventional MRI examinations. In a study done by Boxheimer et al with 42 patients, deplaced meniscal tears had been better demonstrated with kinematic MRI while the knee was in flexion position (9).…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…In this study both sensitivity and specificity values of kinematic MRI had been found to be higher than conventional MRI examinations. In a study done by Boxheimer et al with 42 patients, deplaced meniscal tears had been better demonstrated with kinematic MRI while the knee was in flexion position (9).…”
Section: Discussionmentioning
confidence: 97%
“…The dynamic properties of normal menisci during knee joint movement have been evaluated in different studies (7,9). The menisci are mobile, and permit anteriorposterior and medial-lateral movements during flexion and extension of the knee (8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations